2020
DOI: 10.13106/jafeb.2020.vol7.no6.485
|View full text |Cite
|
Sign up to set email alerts
|

Critical Factors Affecting the Salaries of Employees of Manufacturing Enterprises in Vietnam

Abstract: The study aims to identify and measure factors affecting the salaries of employees in manufacturing enterprises in Hanoi, the important area of Vietnam's economy. We conducted a questionnaire consisting of 31 observation variables with a 5-point Likert scale. Independent variables were measured from 1 "without effect" to 5 "strongly". Based on the literature review and results of interviews, a total of 350 questionnaires were sent to participants; 300 of them met the standards and were subject to be analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…• β 0 is the intercept of the model • β 1 → β 13 : respectively estimated coefficients of variables in the model, including independent variables and control variables. • λ is the inverse Mills factor, determined from step 1 • i is the i firm to be surveyed • t is the year, 2009, 2012 and 2016 • ε it and u it : are the model errors ROS (dependent variable): measured as a ratio of return on sales (Do, 2020;Xiao et al, 2013). DOI (Degree of Internationalization): We choose the export value over total sales as a proxy for the degree of internationalization of the firm (Capar & Kotabe, 2003).…”
Section: Estimation Methodsmentioning
confidence: 99%
“…• β 0 is the intercept of the model • β 1 → β 13 : respectively estimated coefficients of variables in the model, including independent variables and control variables. • λ is the inverse Mills factor, determined from step 1 • i is the i firm to be surveyed • t is the year, 2009, 2012 and 2016 • ε it and u it : are the model errors ROS (dependent variable): measured as a ratio of return on sales (Do, 2020;Xiao et al, 2013). DOI (Degree of Internationalization): We choose the export value over total sales as a proxy for the degree of internationalization of the firm (Capar & Kotabe, 2003).…”
Section: Estimation Methodsmentioning
confidence: 99%
“…Buying behaviour is the decision processes and acts of people involved in buying and using products (Doan, 2021). Usually the buying behaviour takes many forms of consumer's choices that can vary depending on a broad set of factors such as: earnings, demographics, social and cultural factors (Mansoor and Jalal, 2011).…”
Section: Consumer Buying Behaviour and Product-harm Crisismentioning
confidence: 99%
“…A good amount of pay significantly impacts teachers' inner satisfaction and can also be seen as a criterion for deciding whether or not to work. Various researchers found that their respondents respond, "they will remain on their teaching jobs if the salary is raised and incentives are provided" (Card, 2012;DO, 2020;Shi & Sicular, 2010).…”
Section: Salaries and Remuneration Of Teachersmentioning
confidence: 99%